Herança de caracteres agronômicos e avaliação de fosfitos e fosfonatos em soja - Shigihara, Decio (2018)
The competitiveness in agribusiness combined with the most productive cultivars makes genetic improvement play a crucial role in the soybean crop. And the repetitive use of the same mechanism of action of the fungicides allowed the appearance of diseases more resistant to the fungicides, and the inducers of resistance can provide resistance management and cause to work with a greater number of mechanisms of action against the phytopathogens. In this way, this dissertation is subdivided in: literature review about the culture, soybean breeding, genetic parameters, diseases and inductors of resistance, and two chapters: In the chapter 1 the objective was to evaluate soybean cultivars as a reaction to diseases with use of fungicides and association with phosphites of copper, potassium and copper phosphonate. Five soybean cultivars (UFUS 7415, Syn 13671 IPRO, TMG 7062 IPRO, BMX Desafio RR and P98Y30) were evaluated, which were submitted to treatments: without fungicide, pyraclostrobin and epoxiconazole, pyraclostrobin and epoxiconazole + potassium phosphite, pyraclostrobin and epoxiconazole + copper phosphite and pyraclostrobin and epoxiconazole + copper phosphonate. A randomized block design with subdivided plots was used, where each plot consisted of four rows of five meters spaced 0.50 meters between rows, and the evaluations were carried out in the two plants, scoring 0.50 meters from the ends. The evaluation of the diseases was carried out using a visual scale of notes: Asian rust (CANTERI; GODOY, 2003) and for Septoria glycines and Cercospora kikuchii (MARTINS, 2004), and productivity and weight of 100 grains were evaluated. The experiment was carried out at the Capim Branco farm, belonging to the Federal University of Uberlândia-UFU in the 2016/17 harvest. It was observed that UFUS 7415 obtained lower severity to the attack of Asian rust, cercospora and septoriose, and the cultivar BMX Desafio RR was the one that presented higher yields with the use of resistance inducers. In chapter 2, the objective was to perform inheritance analyzes in two soybean populations aiming at heritability and grain yield. The experiment was carried out at the Capim Branco farm of the Federal University of Uberlândia-UFU in the 2016/17 and 2017/18 crops, with the generations P1, P2, F1 and F2 coming from 2 populations between cultivars UFUS 7415 and NS 5909 RG and CD2737 IPRO and NS5909 RG. Initially, hybrids were artificially grown in a greenhouse, and after harvesting, their seeds were sown at field level. The height of the plant was evaluated at flowering, maturation and insertion of the first pod, at flowering and maturation, days for flowering and maturation, plant weight and yield per plant. In the population 1, the heritability varied from 30.08% for number of flowering to 80.79% for number of days for flowering, already in population 2, 25.12% in number of flowering, and 76, 09% in number of days for flowering. In F2 of population 1, the existence of transgressive segregants for number of days for flowering and grain yield was verified in terms of number of nos in flowering and number of totals. The genetic variance and heritability of the agronomic traits of the F2 population, from populations 1 and 2, allow promising genotypes in a soybean breeding program.